2021
DOI: 10.11604/pamj.2021.39.154.27623
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-adherence to antiretroviral therapy among HIV-infected adolescents aged 15-19 years: a snapshot from the Mother and Child Center in Yaounde, Cameroon

Abstract: Introduction non-adherence to antiretroviral therapy (ART) constitutes the main cause of therapeutic failure among HIV-infected adolescents, especially in the aged group 15 to 19 years. We aimed to determine factors associated with this non-adherence in this specific population. Methods we conducted a cross-sectional study at the Mother and Child Center in Yaounde from August to October 2018. Delayed clinic appointment was referred to as defaulters. Non-adherence was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
0
13
1
2
Order By: Relevance
“…This low rate of non-adherence could be explained by the therapeutic education and awareness that PLHIV received in ART clinics about the advantages of adherence and the disadvantages of non-adherence. The rate of non-adherence found in this study was lower than the one found in studies carried out in Gabon, Ethiopia and Cameroon, [29][30][31] and higher than the one reported by in Madagascar (2023). [32] The current ndings also differed from those observed in certain towns in the DRC.…”
Section: Discussioncontrasting
confidence: 75%
“…This low rate of non-adherence could be explained by the therapeutic education and awareness that PLHIV received in ART clinics about the advantages of adherence and the disadvantages of non-adherence. The rate of non-adherence found in this study was lower than the one found in studies carried out in Gabon, Ethiopia and Cameroon, [29][30][31] and higher than the one reported by in Madagascar (2023). [32] The current ndings also differed from those observed in certain towns in the DRC.…”
Section: Discussioncontrasting
confidence: 75%
“…Table 1 allows seeing the articles (A) included according to the general characteristics: author/year, title, information source (IS), which indicates where the study was made available, locus, and language. The results of this review evidenced that the articles included were developed in Botswana (12), the United Kingdom (13), Malawi (14), Kenya (15), Ghana (16), Cameroon (17), and Cape City (7), and published in the English language between 2013 and 2021.…”
Section: Resultsmentioning
confidence: 97%
“…Some sociodemographic conditions, such as being male and single, socioeconomic factors and school status proved to be associated with difficulty adhering to the treatment among adolescents and young people with HIV/AIDS (5,12,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations